The Effect of Corporate Governance, Leverage and External Audit Quality on Profit Management in Companies Listed on the Idx In 2018-2022 - Nunuk Novianti; Indra Wijaya; Ani Febianingsih (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
Management, as well as those responsible for all company operational activities, can use their authority to influence financial reports. This research aims to analyze and determine the influence of Corporate Governance, Ownership Structure, Leverage and External Audit Quality on Profit Management in Companies Listed on the Indonesia Stock Exchange (IDX ) in 2018 - 2022. The type of research used is quantitative descriptive. This research uses secondary data from financial reports with documentation techniques. The population in this research are companies listed on the Indonesia Stock Exchange (IDX ) in 2018 - 2022. The sample was determined using the purpose sampling method, so there were 36 (thirty-six) companies studied that met the requirements. Hypothesis testing uses the SEM-PLS (Structural Equation Model – Partial Least Square) program. The research results show that Corporate Governance has a significant influence on Leverage and Profit Management, while others do not. However, leverage does not influence earnings management. Corporate governance significantly influences earnings management, and audit quality does not affect earnings management.